2016
DOI: 10.1515/jpem-2015-0158
|View full text |Cite
|
Sign up to set email alerts
|

Use of the triglyceride to HDL cholesterol ratio for assessing insulin sensitivity in overweight and obese children in rural Appalachia

Abstract: Background Studies have suggested that triglyceride to HDL-cholesterol ratio (TRG/HDL) is a surrogate marker of insulin resistance (IR), but information regarding its use in pediatric patients is limited. Objective This study investigated the ability of TRG/HDL ratio to assess IR in obese and overweight children. Subjects The sample consisted of de-identified electronic medical records of patients aged 10–17 years (n = 223). Materials and methods Logistic regression was performed using TRG/HDL ratio as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A strong correlation between the TG/ HDL-C and HOMA-IR was confirmed in a cross -sectional study of the Korean population (Kang et al, 2012;Park et al, 2016) and in indigenous Argentinean children (Hirschler et al, 2013). Similar results were obtained in groups of overweight and obese children (Bridges et al, 2016;Iwani et al, 2017), in which the relationship between the TG/HDL-C ratio and the hiperinsulinemic -euglicemic clamp (Giannini et al, 2011), and other indirect measurements of insulin resistance, such as QUICKI (Olson et al, 2012) and WBISI (whole body insulin sensitivity index) (Giannini et al, 2011), were documented. Moreover, Giannini and co-workers (Giannini et al, 2011) found that this association is significant only in obese Caucasian children, but not in Hispanic or African American children, so the TG/ HDL-C ratio may be ethnically dependent.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A strong correlation between the TG/ HDL-C and HOMA-IR was confirmed in a cross -sectional study of the Korean population (Kang et al, 2012;Park et al, 2016) and in indigenous Argentinean children (Hirschler et al, 2013). Similar results were obtained in groups of overweight and obese children (Bridges et al, 2016;Iwani et al, 2017), in which the relationship between the TG/HDL-C ratio and the hiperinsulinemic -euglicemic clamp (Giannini et al, 2011), and other indirect measurements of insulin resistance, such as QUICKI (Olson et al, 2012) and WBISI (whole body insulin sensitivity index) (Giannini et al, 2011), were documented. Moreover, Giannini and co-workers (Giannini et al, 2011) found that this association is significant only in obese Caucasian children, but not in Hispanic or African American children, so the TG/ HDL-C ratio may be ethnically dependent.…”
Section: Discussionsupporting
confidence: 78%
“…Due to the fact that measurements of TG and HDL-C concentrations are routine and cost-effective outpatient tests, they would greatly facilitate the assessment of reduced insulin sensitivity. Some studies, however, suggest that the relationships described above do not apply to all children and all ethnic groups (Giannini et al, 2011;Sumner et al, 2005;Bridges et al, 2016). There is a need for well-planned studies to confirm the usefulness of the TG/HDL-C ratio in identification of children with a high risk of development of insulin resistance and other obesity-related cardiometabolic disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…This score is modified version proposed by Viitasalo et al ( 16 ). Specifically, we used HOMA-IR in lieu of fasting glucose and insulin, as this index has been shown to be a better assessment of glycemic homeostasis in children than glucose or insulin alone ( 17 19 ); included HDL and triglycerides individually rather than as a ratio given evidence of limited utility of this ratio in children ( 20 ); and used SBP instead of the average of SBP and DBP since SBP is more reliably measured in children and is a stronger predictor of future health ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although the difference between 2.5 and 3.16 may not seem significant, the choice of a cutoff value can have a large impact when determining the prevalence of insulin resistance in a population or identifying factors that contribute to its development. For example, in our previous study 34 of overweight and obese Appalachian children, 82% of the patients would have been classified as insulin resistant using 2.5 as a cutoff value, whereas the use of 3.16 would have resulted in a prevalence of 69%. These differences greatly complicate comparisons between studies and impede the development of practice guidelines.…”
Section: Discussionmentioning
confidence: 95%